PKM KOMPETENSI GURU DALAM PEMANFAATAN TEKNOLOGI AI SEBAGAI PENDUKUNG PEMBELAJARAN DI SMKN 1 BANTAENG - Susanto, Cucut; Nurdiansah, Nurdiansah; Hardi, Hardi; Marsa, Marsa; Rauf, Abdul (Yayasan Education and Social Center, 2023)
This Community Service Research, funded by the Makassar Dipa University Foundation, is intended as a form of approach offered to overcome the problems that exist at SMKN 1 Bantaeng. The problem that is often faced by SMKN 1 Bantaeng is in the teaching process to students. The ability of teachers to teach using the Gamma App application based on Artificial Intelligence, especially regarding presentations, is currently still not used, especially by teachers at SMKN 1 Bantaeng, due to limited knowledge in managing it to teach students. AI (Artificial Intelligence) based learning media training as a means to transfer subjects by utilizing the Gamma App application. This learning media is an activity to optimize teaching and learning for students at SMKN 1 Bantaeng. With the current acceleration of technological development, if a teacher still uses teaching techniques manually, it will be left behind and boring for a student. Without training activities that are constructive in nature for both personal and group interests, it will result in lagging behind in utilizing animation media as a means for teaching. As a result of the PKM training on AI-based learning media (Gamma App) at SMKN 1 Bantaeng, teachers received material on Introduction to Animation Media, Introduction to Gamma App and other tools. Meanwhile, for practical activities: Making learning materials for each participant according to their lesson, Determining the target students being taught so they can understand the lesson. All the activities trained have gone well and really helped the learning and teaching of SMKN 1 Bantaeng teachers